Quem são? Para onde vão?: o segmento aéreo regional no Brasil - Ana Paula Camilo Pereira (Confins)
This article discusses the Brazilian airline sector with emphasis on the regional segment. In this context, the aim is to reveal the importance of the Brazilian regional airline segment regarding the densification of routes in the country and the performance of airlines in terms of territorial scale and business strategy. This approach highlights such as the urban hierarchy is juxtaposed to the airport hierarchy, leading to understand that cooperation strategies are processed as a business necessity for survival of regional airlines that are subordinated of the territorial operations of the leading Brazilian airline market. This interest is mainly as a way to analyze the representativeness of this segment in the strategic relationship between the airlines of different sizes and territorial performances. In short, the submission of regional airline segment reveals the market contradictory logic between the companies in the Brazilian airline sector.